Pengaruh Pengembangan Cuff ETT Menggunakan Spuit dan Cuff-Inflator terhadap Denyut Nadi dan Tekanan Darah Pasien Intubasi - Hikayati (Jurnal Keperawatan Soedirman, 2014)
The ETT cuff is used to prevent air leak and aspiration. A high compliance ETT cuff in adult usually to prevent air leakage. ETT cuff should be inflated in the therapeutic range, because as it may results underinflation and overinflation that will influence the hemodynamic such as heart rate and blood pressure. This study is to assess the effect of inflating ETT cuff using syringes and cuff inflator on the pulse rate and blood pressure changes. This quasi-experiment study applied cross over design to 21 intubated patients. The control group using syringe inflating ETT cuff, while the intervention group using a cuff-inflator. Pulse rate and blood pressure changes at the first intervention and after 4-5 hours were observed. Collected data were analyzed using paired t- test. The results show that inflating of ETT cuff using a syringe and cuff inflator had no significant on both measurements series to pulse rate (p=0.189), sistolic blood pressure (p=0.353), and diastolic (p=0.180). Wheter cuff spuit or cuff inflator do not affect pulse rate and blood pressure. ETT cuff inflation should be considered to maintain ideal pressure and to minimize complication due to underinflation and overinflation.